PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA - Novi Nurvitasari; Firman Jaya; Siti Seituni (PENDIDIKAN SAINS DAN TEKNOLOGI, 2021)
ABSTRACT This study aims to determine the effect of Problem Based Learning on the learning outcomes of class VIII students at MTs Sarji Ar-Rasyid. This research is a quantitative research with ex post facto method. Respondents in this study were all students of class VIII MTs Sarji Ar-Rasyid, totaling 24 students. The data collection techniques carried out included Problem Based Learning questionnaires and Social Studies Learning Outcomes. Testing the validity of the instrument using product moment correlation and reliability testing using Cronbach's alpha. Meanwhile, the data analysis test used correlation significance test and simple linear regression. The results of the analysis of the significance of the correlation obtained t_(count ) of 0.665 with a significance value of 0.000 < 0.05 significance level. Regression results obtained 44.3%, this indicates that Problem Based Learning has a positive and significant influence on student learning outcomes.